2007
DOI: 10.1021/bi061783p
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that the Principal CoII-Binding Site in Human Serum Albumin Is Not at the N-Terminus:  Implication on the Albumin Cobalt Binding Test for Detecting Myocardial Ischemia

Abstract: Human serum albumin (HSA) is the most abundant protein in the blood plasma and is involved in the transport of metal ions. Four metal-binding sites with different specificities have been described in HSA: (i) the N-terminal site provided by Asp1, Ala2, and His3, (ii) the site at the reduced Cys34, (iii) site A, including His67 as a ligand, and (iv) the nonlocalized site B. HSA can bind CoII, and HSA was proposed to be involved in CoII transport. Recently, binding of CoII to HSA has attracted much interest due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
94
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(103 citation statements)
references
References 33 publications
7
94
0
2
Order By: Relevance
“…This reduces the ability of albumin to bind to cobalt and hence, this accounts for the generation of IMA [17].…”
Section: Discussionmentioning
confidence: 99%
“…This reduces the ability of albumin to bind to cobalt and hence, this accounts for the generation of IMA [17].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research into the areas of albumin affected to result in increased IMA have focused on the metal binding region at the N terminus of the protein. However, a recent study 28 has suggested that although cobalt may bind at this site transiently, its electronic configuration is better suited to binding at the fatty acid binding sites. We observed a significant relationship between the IMAR and the functionality of these sites, supporting the hypothesis that this is the binding location (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Three binding sites for cobalt were identified, two of which showed greater avidity than the N-terminal binding site. 235 Fatty acid binding to albumin occurs at one of the additional cobalt binding sites with a negative allosteric interaction. It is hypothesised that in myocardial ischaemia, the release of fatty acids results in binding of fatty acids to albumin.…”
Section: Ischaemia-modified Albuminmentioning
confidence: 99%
“…This would then reduce the ability of albumin to take up cobalt and would account for the presence of IMA. 235 If this also produced a conformational change in the albumin affecting the …”
Section: Ischaemia-modified Albuminmentioning
confidence: 99%